Indices of Loading and Propulsive Ability in the Gait of Patients With Chronic Stroke With Equinus Foot Deviation: A Correlation Study - Mazzoli, Davide; Basini, Giacomo; Prati, Paolo; Galletti, Martina; Mascioli, Francesca; Rambelli, Chiara; Zerbinati, Paolo; Campanini, Isabella; Merlo, Andrea (Frontiers in Human Neuroscience, 2022)
In literature, indices of overall walking ability that are based on ground reaction forces have been proposed because of their ease of administration with patients. In this study, we analyzed the correlation between the indices of dynamic loading and propulsion ability of 40 chronic hemiparetic post-stroke patients with equinus foot deviation and a set of clinical assessments of ankle joint deviations and walking ability. Ankle passive and active range of motion and triceps surae spasticity were considered, along with walking speed and three complementary scales of walking ability focusing respectively on the need of assistance, on functional mobility including balance and transfers and on the limitation in social participation. The correlation between the Ground Reaction Force-based indices and both clinical and functional variables was carried out using the non-parametric Spearman correlation coefficient. Both indices were correlated to 8 of the 10 investigated variables, thus supporting their use. In particular dynamic propulsive ability was correlated with all functional scales (rho = 0.5, p<0.01), and has the advantage of being a continuous variable. Among clinical assessments, limited ankle range of motion affected walking ability the most, while spasticity did not. Since the acquisition of ground reaction forces does not require any patient prepping, the derived indices can be used during the rehabilitation period to quickly detect small improvements that over time might lead to the broad changes detectable by clinical scales, as well as to immediately highlight the lack of these improvements, thus suggesting adjustments to the ongoing rehabilitation approach.